Electrohydrodynamic Jet Printing of 1D Photonic Crystals: Part II—Optical Design and Reflectance Characteristics. Issue 10 (26th August 2020) - Iezzi, Brian; Afkhami, Zahra; Sanvordenker, Shea; Hoelzle, David; Barton, Kira; Shtein, Max
Abstract: Additive manufacturing systems that can arbitrarily deposit multiple materials into precise, 3D spaces spanning the micro‐ to nanoscale are enabling novel structures with useful thermal, electrical, and optical properties. In this companion paper set, electrohydrodynamic jet (e‐jet) printing is investigated for its ability in depositing multimaterial, multilayer films with microscale spatial resolution and nanoscale thickness control, with a demonstration of this capability in creating 1D photonic crystals (1DPCs) with response near the visible regime. Transfer matrix simulations are used to evaluate different material classes for use in a printed 1DPC, and commercially available photopolymers with varying refractive indices ( n = 1.35 to 1.70) are selected based on their relative high index contrast and fast curing times. E‐jet printing is then used to experimentally demonstrate pixelated 1DPCs with individual layer thicknesses between 80 and 200 nm, square pixels smaller than 40 µm across, with surface roughness less than 20 nm. The reflectance characteristics of the printed 1DPCs are measured using spatially selective microspectroscopy and correlated to the transfer matrix simulations. These results are an important step toward enabling cost‐effective, custom‐fabrication of advanced imaging devices or photonic crystal sensing platforms. Abstract : Electrohydrodynamic jet printing is used to create patterned arrays of multimaterial photopolymer 1D photonic crystals. Patterns are demonstrated with in‐plane dimensions below 40 µm, layer thicknesses less than 100 nm, and surface root mean square roughness below 20 nm. This novel fabrication method can enable rapid, reconfigurable manufacturing of custom photonic sensing arrays.